Early childhood infectious diseases and the development of asthma up to school age: a birth cohort study. Issue 7283 (17th February 2001) - Illi, Sabina; Mutius, Erika von; Lau, Susanne; Bergmann, Renate; Niggemann, Bodo; Sommerfeld, Christine; Wahn, Ulrich
Abstract: Objective: To investigate the association between early childhood infections and subsequent development of asthma. Design: Longitudinal birth cohort study. Setting: Five children's hospitals in five German cities. Participants: 1314 children born in 1990 followed from birth to the age of 7 years. Main outcome measures: Asthma and asthmatic symptoms assessed longitudinally by parental questionnaires; atopic sensitisation assessed longitudinally by determination of IgE concentrations to various allergens; bronchial hyperreactivity assessed by bronchial histamine challenge at age 7 years. Results: Compared with children with 1 episode of runny nose before the age of 1 year, those with 2 episodes were less likely to have a doctor's diagnosis of asthma at 7 years old (odds ratio 0.52 (95% confidence interval 0.29 to 0.92)) or to have wheeze at 7 years old (0.60 (0.38 to 0.94)), and were less likely to be atopic before the age of 5 years. Similarly, having 1 viral infection of the herpes type in the first 3 years of life was inversely associated with asthma at age 7 (odds ratio 0.48 (0.26 to 0.89)). Repeated lower respiratory tract infections in the first 3 years of life showed a positive association with wheeze up to the age of 7 years (odds ratio 3.37 (1.92 to 5.92) for 4 infections v 3 infections). Conclusion: Repeated viral infections other than lower respiratory tract infections early in life may reduce the risk of developing asthma up to school age.